PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN KESEHATAN RAWAT JALAN DI RSUD BENGKALIS KECAMATAN BENGKALIS - Ami Pratiwi; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine people's perceptions of the quality of Bengkalis hospital services and the factors that influence people's perceptions of Bengkalis Hospital services.This study used a quantitative research method with a population of 4,200, namely the average monthly number of Bengkalis hospital patients with a sample size of 100 respondents using the Slovin formula, sample selection using simple random techniques. The results of this study indicate that the public perception of the quality of Bengkalis hospital services seen from the overall dimensions of service characteristics is good, seen from the perceptions of outpatients most of them have positive perceptions although some still have negative perceptions of Bengkalis Hospital services. Then the factors that influence society due to the influence of community experience, from mood because not all good moods will have a good perception but depending on the services they get, then there is knowledge of patients so that not all good perceptions of the comfort of the waiting room are fulfilled. Keywords: Perception, Health Services, hospital